Peran Pendidikan Kristen dalam Keluarga Yang bercerai (Jurnal Pendidikan Agama dan Teologi, 2023)
Divorce is a problem that can affect every family. The impact of divorce can be felt by husbands, wives especially on children. In modern life, now divorce is considered as a way to solve problems in the family, but this is not necessarily successful and the problem will be resolved properly. Christian Religious Education plays a role in the case of divorce in Christian families. The method used in this article is the Systemic Literature Review method, which collects a large number of theories originating from books, research and journals related to the research topic. The results of this study are that Christian education becomes a bridge and becomes a preventive action taker before the family is divorced.